Effects of Different Inoculation Regimes of Torulaspora delbrueckii and Oenococcus oeni on Fermentation Kinetics and Chemical Constituents of Durian Wine - Lu, Y.; Chua, J.-Y.; Voon, M.K.W.; Huang, D.; Lee, P.-R.; Liu, S.-Q. (South African Journal of Enology and Viticulture, 2017)
This work evaluated the effects of inoculation time of Oenococcus oeni on the kinetics of fermentation and chemical constituents of durian wine produced using a non-Saccharomyces yeast, Torulaspora delbrueckii. The growth of T. delbrueckii in mixed-culture fermentations was significantly adversely affected by the presence of O. oeni, and the growth of malolactic bacteria was also affected by the metabolism of yeast during fermentation. The level of ethanol produced in simultaneous alcoholic and malolactic fermentation (SIM, 6.93%, v/v) was comparable to that in the Saccharomyces cerevisiae EC-1118 control (6.75%, v/v); both levels were relatively higher than that in the T. delbrueckii Biodiva control (6.39%, v/v) and the other two sequential fermentations (oenococci inoculated after four and seven days of alcoholic fermentation, SEQ 4th, 6.34% and SEQ 7th, 6.33% v/v respectively). The final concentrations of organic acids and esters in the mixed-culture wines were correlated with the inoculation time of O. oeni. SIM produced relatively higher levels of ethyl esters (ethyl esters of hexanoate, octanoate, decanoate and lactate) and acetate esters (ethyl acetate and isoamyl acetate) than those in SEQ 4th, SEQ 7th and the Biodiva control. This suggests that SIM would contribute fruity aroma properties to and modulate the mouthfeel of durian wine. The production of 3-(ethylthio)-1-propanol could compensate for the weak onion-like odour caused by the decrease in initial volatile sulphur compounds. Overall, this research suggests that SIM treatment is an effective way to produce durian wine with higher ester production.